MODEL KURIKULUM PROGRAM STUDI S-1 MANAJEMEN INFORMASI KESEHATAN BERBASIS KERANGKA KUALIFIKASI NASIONAL INDONESIA - Hosizah Hosizah (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
Indonesian Qualifications Framework (IQF) established in 2012 refers the Indonesian embodiment on quality and national identity associated with national education and training system. IQF is levelling of competences and qualifications framework to reconcile, equalize, and integrate the fields of education and job training and work experience in order to award the work in accordance with the recognition of the competence structure of employment in various sectors. There are nine (9) levels of IQF qualifications, starting with the first is lowest to ninth qualification is highest. The Bachelor of Science Health Information Management at the sixth level of IQF which currently did not exist a core curriculum standard in Indonesia, therefore it was needed to formulate a Baccalaureate Degree Curriculum on Health Information Management Model based on IQF. This was conducted on Bachelor of Science Health Information Management Esa Unggul University Jakarta in August-September 2016 by using the Guidelines of Curriculum Directorate of Higher Education and Student Learning, Ministry of Research Technology and Higher Education Higher Education Republic Indonesia. There are 5 (five) the Bachelor of Health Information Management Profiles successfully established include A Specialist Coding Clinical, A Data Analyst and Manager of Health Information, A Manager of Health Information Management Department, A Specialist Clinical Documentation Improvement (CDI), An Initiator on Designer and developer Electronic Health Records or Electronic Medical Records. Total credits 144 and eight semesters or four years.